Lp95, a novel leptospiral protein that binds extracellular matrix components and activates e-selectin on endothelial cells - Atzingen, Marina V. (2009)
The study of a predicted outer membrane leptospiral protein encoded by the gene LIC12690 in mediating the adhesion process. The gene was cloned and expressed in Escherichia coli BL21 (SI) strain by using the expression vector pAE. The recombinant protein tagged with N-terminal hexahistidine was purified by metal-charged chromatography and used to assess its ability to activate human umbilical vein endothelial cells (HUVECs).